Identification of commonly used medicinal plants in Kangkar Pulai and their therapeutic evaluation as anti-diabetic - Alsarhan, Ali Ata Zidan (2015)
Medicinal plants have been used as traditional medicines for treatment of diseases such as diabetes mellitus. However, scientific information to support the claims of herbal medicine practitioners based on Use Value (UV) and Informant Consensus Factor (ICF) is largely unexplored. The aim of this study is to screen common medicinal plants and to evaluate their traditional use through an ethnopharmacological survey at Kangkar Pulai, Johor, Malaysia. Data were collected from the community through open interviews, determining the relative importance of the species surveyed and calculating the UV and ICF in relation to the medicinal plant uses. A total of 38 plant species belongs to 28 families were documented. Based on the results of ethnopharmacological survey, Orthosiphon stamineus Benth and Momordica charantia L recorded the highest Use Values (0.32 and 0.24) to treat diabetes. The results of antioxidant tests revealed that the total phenolic content (TPC) of O. stamineus is 71.70 ± 0.85 mg (GAE)/g and total flavonoid content (TFC) is 44.71 ± 0.75 mg (CE)/g. Further study was carried out to examine the effects of oral administration of O. stamineus extract in the treatment of diabetes in normal and alloxan-induced diabetic rats. Forty rats were divided into four groups of 10 each. Group A (control) consisted of normal rats receiving 2 mL (10 mL/kg bwt) of normal saline on daily basis, whereas group B consisted of diabetic rats treated with 1 mL (120 mg/kg bwt) of O. stamineus extract. Group C consisted of diabetic rats treated with 1 mL (150 mg/kg bwt) of Metformin. Group D consisted of untreated diabetic rats acted as negative control. Group B, C and D were injected intrapertonially with alloxan (150 mg /kg bwt). Diabetic group B rats treated with O. stamineus extract showed significantly (p <0.05) low blood glucose level compared to group D (untreated diabetic rats). Similarly diabetic group B rats consumed significantly lower daily food and water intake at significant level p <0.05 compared to group D (untreated diabetic rats). Diabetic group B rats treated with O. stamineus extract showed significantly higher body weight at significant level p <0.05 compared to group D (untreated diabetic rats). Diabetic group B rats treated with O. stamineus extract showed lower serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and higher high-density lipoprotein cholesterol (HDL-C) at significant value (p < 0.05) compared with group D (untreated diabetic rats). A significant decrease of total protein, albumin and creatinine was observed in the plasma of group B rats after being treated with O. stamineus extract compared with group D. Additionally, immunohistochemistry results showed that the levels of heat shock protein 70 (HSP70) and inducible nitric oxide synthase (iNOS) of group B diabetic rats were brought back to near normal range after being treated with O. stamineus extract at significant value (p < 0.05) compared with group D (untreated diabetic rats). In conclusion, O. stamineus extract exhibited antidiabetic activity in alloxan-induced diabetic rats. Thus, the present findings also support the potential use of O. stamineus extract as a remedy for hyperglycemia.